2001
DOI: 10.1016/s0378-1127(00)00631-9
|View full text |Cite
|
Sign up to set email alerts
|

Breeding bird assemblages of hurricane-created gaps and adjacent closed canopy forest in the southern Appalachians

Abstract: We studied breeding bird assemblages in forest gaps created in 1995 by Hurricane Opal at the Bent Creek Experimental Forest in Asheville, NC. We hypothesized that forest gaps and adjacent closed-canopy forest would differ in bird density, richness, diversity, and relative abundances of some species. To test this hypothesis we censused breeding bird assemblages for 2 years in 12 gaps (0.1±1.2 ha) and 12 adjacent closed canopy controls using strip transects. Gaps had more coarse woody debris, shrub cover, brushp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
46
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 18 publications
8
46
0
1
Order By: Relevance
“…As the number of vegetation layer increases, the number of available niches also increases and so does the diversity of avian species. This is similar to a study by Greenberg and Langham (2001) The insignificant seasonal difference in the diversity of bird species within the same forest type in the present study is in agreement with Symth (1974), Karr (1976), and Karr and Freemark (1993). This might be due to the presence of structurally complex vegetation types that buffer the effect of seasonality.…”
Section: Relative Abundancesupporting
confidence: 94%
“…As the number of vegetation layer increases, the number of available niches also increases and so does the diversity of avian species. This is similar to a study by Greenberg and Langham (2001) The insignificant seasonal difference in the diversity of bird species within the same forest type in the present study is in agreement with Symth (1974), Karr (1976), and Karr and Freemark (1993). This might be due to the presence of structurally complex vegetation types that buffer the effect of seasonality.…”
Section: Relative Abundancesupporting
confidence: 94%
“…However, our results are consistent with several previous studies that suggest mature forest species occupy early successional areas during the post-fledgling period. For example, Hooded Warblers were found to be more abundant in hurricane caused forest gaps in southern Appalachian forests (Greenberg et al, 2001) and in areas with 60% hemlock (Tsuga canadensis) mortality in the northeastern United States forests (Tingley et al, 2002) compared with undisturbed areas. Likewise, Hunt (1998) found that early successional habitats in Vermont and New Hampshire forests may function as reproductive sources for the American Redstart when compared with mature forests.…”
Section: Discussionmentioning
confidence: 99%
“…In both taxonomic groups, one may identify the ''winners'' and ''losers'' of the salvage logging. This highly diversified reaction for different disturbing regimes or silvicultural treatments seems to be a common pattern (Greenberg and Lanham 2001;Venier and Pearce 2007;Kolbin 2008;Grimbacher and Stork 2009;_ Zmihorski 2010). In general, it seems that dead wood and natural structure of the windthrow left for natural regeneration positively affected forest dwelling species and saproxylic organisms (Bässler and Müller 2010;Müller et al 2010), whereas abundance of open-area specialists increased as a result of windthrow management.…”
Section: Discussionmentioning
confidence: 97%